Clinical applications of circulating tumor cells in metastasis and therapy - Chuan Yang; Can Liu; Chenglai Xia; Liwu Fu (Journal of Hematology & Oncology)
Abstract Circulating tumor cells (CTCs), which serve as an early indicator of tumors in peripheral blood, are closely associated with unfavorable prognoses in individuals with cancer. Gaining a thorough understanding of the heterogeneity and specific trajectory of CTCs during metastasis can yield valuable insights for the development of effective cancer treatment strategies. This review critically examines the contemporary knowledge of the in vivo process of CTCs, with a focus on the four key stages: dissemination, homing, colonization, and macro-metastasis. Each stage is discussed in terms of its associated characteristics, including epithelial-mesenchymal transition (EMT), dormancy, organotropism, and awakening. We also discuss recent advancements in CTC isolation, detection, cultivation and its potential applications. Additionally, it provides a comprehensive elucidation of the intricate mechanisms of immune evasion and drug resistance in CTCs, aiming to identify novel targets for cancer therapy. Finally, an overview of CTC interventions is presented, which may facilitate the development of personalized therapeutic approaches for patients and improve their metastasis-free prognostic outcomes.